Microprojectile bombardment assisted agroinfection increases transformation efficiency of Withania somnifera (L.) - Patel, Neha; Patel, Parth; Kumari, Uma; Kendurkar, Shuchishweta V; Khan, Bashir M (Research in Biotechnology, 2014)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 11.0pt; line-height: 115%; font-family: "Book Antiqua","serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Withania somnifera <span style="font-size: 11.0pt; line-height: 115%; font-family: "Book Antiqua","serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">(L.) Dunal, an evergreen shrub distributed throughout the drier parts of India, is well known for its medicinal properties. Three different approaches were employed towards development of an efficient transformation system in Withania somnifera, namely Agrobacterium tumefaciens-mediated transformation, microprojectile bombardment and microprojectile bombardment assisted agroinfection. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->